2010
DOI: 10.1038/ncomms1052
|View full text |Cite|
|
Sign up to set email alerts
|

Current drive at plasma densities required for thermonuclear reactors

Abstract: Progress in thermonuclear fusion energy research based on deuterium plasmas magnetically confi ned in toroidal tokamak devices requires the development of effi cient current drive methods. Previous experiments have shown that plasma current can be driven effectively by externally launched radio frequency power coupled to lower hybrid plasma waves. However, at the high plasma densities required for fusion power plants, the coupled radio frequency power does not penetrate into the plasma core, possibly because o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
140
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(164 citation statements)
references
References 38 publications
18
140
0
1
Order By: Relevance
“…Prior investigation of LHCD at such high densities was conducted in circular, limited tokamaks such as Alcator C [24] and FTU [25,18,19]. Although the experiments on C-Mod show no dependence on elongation, the difference between limited and diverted plasmas is significant and this may explain the unexpectedly low density limit encountered for diverted discharges in C-Mod.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior investigation of LHCD at such high densities was conducted in circular, limited tokamaks such as Alcator C [24] and FTU [25,18,19]. Although the experiments on C-Mod show no dependence on elongation, the difference between limited and diverted plasmas is significant and this may explain the unexpectedly low density limit encountered for diverted discharges in C-Mod.…”
Section: Discussionmentioning
confidence: 99%
“…Results from the FTU LHCD experiment suggest that the LHCD density limit can be overcome by raising the temperature in the plasma edge (r/a > 0.8) [18,19]. The I-mode confinement regime on C-Mod consists of an H-mode like temperature pedestal at the plasma edge with an L-mode like density profile [20,21,22].…”
Section: Sensitivity To Plasma Temperaturementioning
confidence: 99%
“…Reactor relevant high plasma density regimes have faced the LHCD tool with the challenge of effectively penetrating the main plasma without excessive power dissipation of the coupled radio frequency (RF) power at the edge. LHCD experiments on many tokamaks (Pericoli-Ridolfini, Giannone & Bartiromo 1994;Cesario et al 2010;Wallace et al 2010;Cesario et al 2011) have shown a decrease in non-thermal tails and a drop in bremsstrahlung emission much steeper than 1/n e at high densities, which is stronger than expected based on current models. Similar results (Ding et al 2013a have also been reported in EAST.…”
Section: Lhcd Capability At High Densitymentioning
confidence: 93%
“…It is well known [3,4] that the spectral broadening of the launched LH (pump) wave at 3.7GHz is caused by scattering from low frequency density fluctuations at the plasma edge, while lower sideband appearance can be related to parametric decay of the pump wave into another LH wave (the lower sideband) and a low frequency Fig. 1(a), were analyzed versus the launched LH power, P LH , line averaged plasma density, n e , and magnetic field, B T .…”
Section: Rf Spectra Measurementsmentioning
confidence: 99%
“…Furthermore, a new LH-related diagnostic based on RF spectra measurements was setup, tested and validated during JET restart. Initial data have been collected and analyzed in order to address important issues regarding the impact of the Parametric Decay Instabilities (PDI) [3,4] on the CD efficiency at high densities. In addition a new RT/FP code was developed at JET in order to study the impact of the real plasma shape and poloidal variations in the launched spectrum on the LH wave power deposition and CD efficiency.…”
Section: Introductionmentioning
confidence: 99%